Presentasi Diri Terkait Oversharing Sertifikat Vaksin Covid-19 pada Tenaga Kesehatan - Ratih Kumala Dewi; Puspita Puji Rahayu (Jurnal Kesehatan, 2022)
Currently the Indonesian government continues to reduce the transmission rate of the Covid-19 virus, one of is by vaccinating health workers who are the first targets and after the vaccine is carried out they will receive legal evidence of a certificate. In the media, of oversharing from social media users is always considered a threat because of the various negative impacts, the high level such as the security of personal data. This type of research is a cross-sectional analytic using a questionnaire which is an online survey to determine the level of awareness of personal data security and self-presentation to health workers regarding oversharing of covid-19 certificates. The population is health workers in Central Java with a sample of 170 respondents. Data analysis used Univariate, bivariate and multivariate analysis using the HAIS-Q adoption questionnaire and self-presentation questionnaire. There is a relationship between gender (p= 0.000) and age (p= 0.000) with the level of awareness of personal data security and the factor most related to the level of awareness of personal data security is self-presentation with criteria Exemplification (Sampling) (OR = 5,103 : p value = 0.004; CI = 95% 1.455 to 12.426). The government should conduct socialization related to the protection of personal data in vaccination certificates so that the public understands and is aware of the information contained therein.